Travel and tourism public relations : an introductory guide for hospitality managers / Dennis E Deuschl - Deuschl, Dennis E
"Travel and Tourism Public Relations outlines the standard PR communications tools of the industry's four major sectors to examine each sector's specialized media, messages, audiences, PR tools, and crises. Chapters include numerous sidebars from industry PR experts containing case histories, checklists, anecdotes and tips."--Jacket.